2014
DOI: 10.1063/1.4876752
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of head-on collision of dust acoustic solitary waves in a strongly coupled complex plasma

Abstract: We investigate the propagation characteristics of two counter propagating dust acoustic solitary waves (DASWs) undergoing a head-on collision, in the presence of strong coupling between micron sized charged dust particles in a complex plasma. A coupled set of nonlinear dynamical equations describing the evolution of the two DASWs using the extended Poincaré-Lighthill-Kuo perturbation technique is derived. The nature and extent of post collision phase-shifts of these solitary waves are studied over a wide range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…8, which shows the trajectories of the two solitons, it can be observed that after the collision the low amplitude soliton in this case gets dragged in the direction opposite to its own propagation, by the high amplitude structure for a while. This is in confirmation with the analytical results obtained by Surabhi et al 42 . This time phase shift is about 5.7ω −1 pd which is shown in Fig.…”
Section: B Head-on Collision Of Different Amplitude Solitonssupporting
confidence: 93%
“…8, which shows the trajectories of the two solitons, it can be observed that after the collision the low amplitude soliton in this case gets dragged in the direction opposite to its own propagation, by the high amplitude structure for a while. This is in confirmation with the analytical results obtained by Surabhi et al 42 . This time phase shift is about 5.7ω −1 pd which is shown in Fig.…”
Section: B Head-on Collision Of Different Amplitude Solitonssupporting
confidence: 93%
“…It is the critical value of the plasma transmission from the fluid phase to a quasisolid structure called the plasma crystal. These results correspond with the simulation results in Reference [17] and with the theoretical study that did not take into account the effect of the structure parameter on the compressibility (i.e., k = 0) in Reference [14].…”
Section: Soliton Shape Changessupporting
confidence: 89%
“…We consider an unmagnetized strongly coupled dusty plasma system with negatively charged inertial dust grains and inertia-less electrons and the ions that can be described by Boltzmann distributions. The dust fluid equations that can describe this system are given as follows [14,21]:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the head on collision between two opposite propagating KdV solitary waves can pass through each other as if without suffering any interaction except for a slight phase shift in their positions. It has been extensively studied by using the extended Poincare-Lighthill-Kuo (PLK) method analytically 20 25 26 27 28 and verified in the experiments 19 . Recently the application scope of the PLK method on the colliding of two KdV solitary waves is studied by using the PIC method 23 .…”
Section: Resultsmentioning
confidence: 99%